Development of a forest carbon and nitrogen model: Pilot application for a Pinus densiflora forest in Central Korea. Issue 4 (2nd October 2019) - Kim, Hyungsub; Kim, Seongjun; Lee, Jongyeol; Chang, Hanna; Roh, Yujin; An, Jiae; Son, Yowhan
Abstract: This study aimed to develop a forest carbon (C) and nitrogen (N) model, known as the Forest Biomass and Dead organic matter Carbon And Nitrogen (FBDCAN), which can be useful under limited input data availability. An N module was designated with three N pools (biomass, dead organic matter, and soil inorganic N) and ten N cycle processes (N deposition, biological N fixation, N mineralization, immobilization, root N uptake, retranslocation, nitrification, N leaching, denitrification, and turnover), and then integrated into an existing forest C model. A pilot application was carried out for a Pinus densiflora forest in Gwangneung Experimental Forests (PGEF), to verify the performance and reliability of the model. The simulated net N mineralization in 2010 (69.91 kg N ha −1  yr −1 ) was within the observed range in PGEF. Furthermore, the simulated N stock (3.91 Mg N ha −1 ) based on the FBDCAN model was consistent with the observed N stock (4.13 Mg N ha −1 ) in PGEF ( r 2 = 0.96 to 0.99). The newly developed forest C and N model could be used for the estimation of N cycle processes, N stock, and C stock, even in regions where the input data availability is low.